Conference Scene: Biomarkers in the next decade. (February 2011) - Gibson, Greg
In the next decade, biomarker research is increasingly likely to incorporate multivariate associations utilizing diverse molecular data types. This meeting surveyed some emerging technologies for profiling on the genomic scale in hundreds of patients, discussed the computational challenges in data reduction and interaction analysis and collated numerous success stories where multiple markers jointly associate with disease.